Cutaneous leishmaniasis situation analysis in the Islamic Republic of Iran in preparation for an elimination plan - Iraj Sharifi; Ahmad Khosravi; Mohammad Reza Aflatoonian; Ehsan Salarkia; Mehdi Bamorovat; Ali Karamoozian; Mahmoud Nekoei Moghadam; Fatemeh Sharifi; Abbas Aghaei Afshar; Setareh Agha Kuchak Afshari; Faranak Gharachorloo; Mohammad Reza Shirzadi; et al. (Frontiers Media S.A., 2023)
Iran has invariably been under the growing public health threat of cutaneous leishmaniasis (CL), a significant barrier to local development that hinders the prevention and control efforts toward eliminating the disease. So far, no comprehensive and in-depth epidemiological analysis of the CL situation has been carried out nationwide. This study aimed to employ advanced statistical models to analyze the data collected through the Center for Diseases Control and Prevention of Communicable Diseases during 1989-2020. However, we emphasized the current trends, 2013-2020, to study temporal and spatial CL patterns. In the country, the epidemiology of CL is incredibly intricate due to various factors. This fact indicates that the basic infrastructure, the preceding supports, and the implementation plan related to preventive and therapeutic measures need crucial support. The leishmaniasis situation analysis is consistent with desperate requirements for efficient information on the control program in the area. This review provides evidence of temporally regressive and spatially expanding incidence of CL with characteristic geographical patterns and disease hotspots, signifying an urgent need for comprehensive control strategies. This information could be a suitable model and practical experience in the Eastern Mediterranean Region, where over 80% of CL is reported.